2020
DOI: 10.12911/22998993/112875
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Pesticides from Wastewater by the Use of Constructed Wetlands

Abstract: The purpose of the work was to determine the efficiency of domestic wastewater treatment contaminated with a mixture of pesticides at varying deposit load. The efficiency of purification in the case of eight pesticides equaled 99.8%, and the removal effect of azoxystrobin reached 93%, while that of thiachloprid-96%. The constructed wetland ensured high removal of organic matter expressed as BOD and COD, as well as reduction in the concentration of nitrogen and phosphorus compounds. Studies showed a clear impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Pesticide removal from agricultural runoff or drain is vital for the protection of the aquatic ecosystem, and environment. CWs have great potential for pesticide removal from wastewater containing agricultural runoff, and stormwater (Ignatowicz et al, 2020; Lv et al, 2017; Tournebize et al, 2017). Several processes, such as adsorption, hydrolysis, microbial degradation, sedimentation, photolysis, and plant uptake play an important role in the removal of pesticides in CWs (Vymazal & Březinová, 2015).…”
Section: Classification Of Cwsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticide removal from agricultural runoff or drain is vital for the protection of the aquatic ecosystem, and environment. CWs have great potential for pesticide removal from wastewater containing agricultural runoff, and stormwater (Ignatowicz et al, 2020; Lv et al, 2017; Tournebize et al, 2017). Several processes, such as adsorption, hydrolysis, microbial degradation, sedimentation, photolysis, and plant uptake play an important role in the removal of pesticides in CWs (Vymazal & Březinová, 2015).…”
Section: Classification Of Cwsmentioning
confidence: 99%
“…The design of CWs and the type of macrophyte species further influence the pesticide removal processes. In one such study, the CWs were found to remove 99.8% of the mixture of eight pesticides using Phragmites australis from domestic wastewater (Ignatowicz et al, 2020). On the basis of review, Tournebize et al (2017) stated that 1% of the total agricultural land or watershed if used as CWs, can potentially reduce >50% of pesticides from the drained watersheds.…”
Section: Classification Of Cwsmentioning
confidence: 99%
“…Sewage is discharged by 66% of water users, 40% of whom discharge contaminated wastewater [Shakhman et al, 2017;Lykhovyd et al, 2018;Bashynska, 2018;Mitryasova et al, 2021;Shakhman and Bystrintseva, 2021]. The Black Sea river basin covers about 60% of the area of all river basins in the region and currently the Regional office of water resources monitor the water bodies condition, assesses irrigated lands, agricultural lands and settlements that are flooded, as well as hydrochemical and radiological control of border water bodies by agreement between the governments of neighboring countries [Farrelly and Brown, 2011;Vlasov and Hryshchankava, 2014;Ignatowicz, 2020].…”
Section: Journal Of Ecological Engineeringmentioning
confidence: 99%
“…Water resource is affected due to the different means of transport of these pesticides such as direct application to water bodies (Schreiner et al 2021), landslides (Butkovskyi et al 2021), or washing of spraying equipment (Becerra et al 2020a;Manasa & Mehta 2020), which are generated as wastewater with pesticides contents (WWPC's), and trigger a series of effects to the environment, human health and living organisms (Van Lexmond et al 2015;Elfikrie et al 2020;Malakootian et al 2020). The main characteristics of these pollutants are related to high toxicity, slow degradation processes, high COD concentrations, and low removal in conventional biological treatments (Ignatowicz 2020;Ge et al 2021;Sarker et al 2021;Yu et al 2021).…”
Section: Introductionmentioning
confidence: 99%